Sistem Monitoring Kecepatan Otoped Listrik Menggunakan Baterai LiFePO4 sebagai Transportasi Alternatif - Ahmad Firyal Adila; Rafli Maulana Abdullah; Irianto Irianto; Diah Septi Yanaratri; Sutedjo Sutedjo; Renny Rakhmawati Renny Rakhmawati (Universitas Darul Ulum, 2025)
Autoped has become a popular alternative in environmentally friendly urban transportation. It uses batteries as the main power source to drive their electric motors. However, efficient and optimal battery usage is essential to maintain the performance and durability of autoped. This study aims to design a speed monitoring system for autoped using LiFePO4 batteries by considering variations in user loads. This monitoring system informs autoped drivers about the speed when used and battery usage. This electric autoped is equipped with a DC brushed motor with a specification of 24 Volt/500 Watt. The speed is measured using a metal proximity sensor that functions without direct contact, thus ensuring consistent measurements and reducing the risk of errors due to physical interaction. In addition, a load cell sensor with a maximum weight measurement of 100 kg is used to classify user's weight which is divided into three variations: 35-45 kg, 46-55 kg, and 56-65 kg. As the main energy source, this system uses a LiFePo4 battery with a specification of 24 Volt/36 Ah. The system was tested on a flat track on the campus, where the scooters were used to support environmentally friendly mobility around the campus area. This test ensured that the designed speed monitoring system was able to provide real-time data on scooter performance based on user weight, as well as support increased efficiency of battery energy use.